Coffin‐Lowry syndrome in a girl with 46, XX, t(X;11)(p22;p15)dn: Identification of RPS6KA3 disruption by whole genome sequencing. Issue 6 (6th April 2020) - Yamoto, Kaori; Saitsu, Hirotomo; Fujisawa, Yasuko; Kato, Fumiko; Matsubara, Keiko; Fukami, Maki; Kagami, Masayo; Ogata, Tsutomu
Abstract: We report a Japanese girl with Coffin‐Lowry syndrome phenotype such as hypertelorism, hypodontia, and tapering fingers and 46, XX, t(X;11)(p22;p15)dn. Whole genome sequencing revealed RPS6KA3 disruption by the translocation, and X‐inactivation analysis indicated preferential inactivation of the normal X chromosome. The results explain the development of an X‐linked disease in this girl. Abstract : We report a Japanese girl with Coffin‐Lowry syndrome phenotype such as hypertelorism, hypodontia, and tapering fingers and 46, XX, t(X;11)(p22;p15)dn. Whole genome sequencing revealed RPS6KA3 disruption by the translocation, and X‐inactivation analysis indicated preferential inactivation of the normal X chromosome. The results explain the development of an X‐linked disease in this girl.